Autobiographische Textüberlieferung im Alten Reich anhand phraseologischer „Cluster“ - Kloth, Nicole (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
There exists a group of texts among the autobiographical inscriptions of the Old Kingdom that, due to their close phraseological relationship, must go back to a common source, and which can be described as “Saqqara group” according to their place of origin. It dates back to the turn from the 5 th to the 6 th dynasty. This group can now be extended by additional autobiographies and furthermore differentiated. The classical creation of a stemma cannot be used, but instead different significant text sequences, which are called “clusters” here, are examined. The texts of this autobiographical cluster, starting from Saqqara, find their prolongation at the beginning of the 6th dynasty in El-Hawawish and it can be observed that they are transferred from higher-ranking officials at the end of the Old Kingdom to lower-ranking officials in the First Intermediate Period.